A Study From a Psychological Perspective of High Performance to Explore the Relationship Among Resource Bricolage, Social Capital, Entrepreneurial Attitude, and Intention - Yuan, Yu-Hsi (Frontiers in Psychology, 2022)
COVID-19 caused a serious increase in competition due to limited resources. Obviously, it influenced the entrepreneurs’ motivation. The entrepreneurial intention, social capital, and resource bricolage ability of individuals were important issues. Thus, exploring an individual’s mindset from a psychological perspective of high performance was the advanced issue to deal with social capital promotion. This study developed an instrument adapted from related scales that consisted of 27 items and four factors: Social Capital, Entrepreneurial Attitude, Resource Bricolage, and Entrepreneurial Intention. The data was collected through an online survey in China and Taiwan by purposive sampling. A total of 692 valid samples provided data for the statistical process. Multiple regression techniques were employed in the data process. The instrument passed the validity and reliability test. Data analysis results showed that Social Capital can positively predict Entrepreneurial Attitude and Entrepreneurial Intention. Further, Entrepreneurial Attitude will affect Entrepreneurial Intention dramatically. Yet, Resource Bricolage Ability has no moderating effect on Social Capital and Entrepreneurial Intention. In addition, Resource Bricolage Ability plays a moderating role between Entrepreneurial Attitude and Entrepreneurial Intention. Moreover, it found that participants demonstrated a high Entrepreneurial Intention when there was a high Entrepreneurial Attitude with high Resource Bricolage Ability when moderating effect was examined. Some practical suggestions are provided for researchers, educators, and entrepreneurs in this study.